Analysis of Interleukin-1 Signaling Alterations of Colon Adenocarcinoma Identified Implications for Immunotherapy - Zhou, Xiaogang; Liu, Yu; Xiang, Jing; Wang, Yuntao; Wang, Qiqian; Xia, Jianling; Chen, Yunfei; Bai, Yifeng (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors(ICIs) have made breakthrough progress in the treatment of various malignant tumors. However, only some patients receiving ICIs can obtain long-lasting clinical effects, while some patients still cannot achieve remission. How to improve the treatment benefits of this part of the population has become a concern of clinicians. IL-1 signaling plays an important role in the tumor microenvironment(TME). However, the relationship between IL-1 signaling mutation status and the prognosis of colon adenocarcinoma(COAD) patients receiving ICIs has not been reported. We downloaded the data of a COAD cohort receiving ICIs, including prognostic data and mutation data. Additionally, we downloaded the data of a COAD cohort from The Cancer Genome Atlas(TCGA) database, including clinical data, expression data and mutation data. Gene set enrichment analysis(GSEA) was used to assess the difference in the activity of some key physiological pathways between the IL-1 signaling mutated-type(IL-1-MT) group and IL-1 signaling wild-type(IL-1-WT) group. The CIBERSORT algorithm was used to evaluate the contents of immune cells in the TME of COAD patients. The multivariate Cox regression model results suggested that IL-1-MT can be used as an independent predictor of better prognosis for COAD patients receiving ICIs(P = 0.03, HR = 0.269, 95% CI: 0.082-0.883). Additionally, IL-1-MT COAD had significantly prolonged OS times(log-rank P = 0.015). CIBERSORT analysis showed that the IL-1-MT group had high infiltration levels of activated dendritic cells(DCs), M1 macrophages, neutrophils, activated natural killer(NK) cells, activated CD4+ memory T cells and CD8+ T cells. Similarly, the IL-1-MT group had significantly upregulated immunogenicity, including tumor mutation burden(TMB), neoantigen load(NAL) and the number of mutations in DNA damage repair(DDR) signaling. GSEA showed that the IL-1-MT group was highly enriched in the immune response and pro-inflammatory mediators. Additionally, the expression levels of immune-related genes, immune checkpoint molecules and immune-related signatures were significantly higher in the IL-1-MT group than in the IL-1-WT group. IL-1-MT may be an independent predictor of good prognosis for COAD patients receiving ICIs. IL-1-MT COAD has a significantly prolonged OS. Additionally, IL-1-MT is associated with significantly increased immunogenicity, numbers of activated immune cells, inflammatory mediators and immune response-related scores.